PENGOLAHAN DATA PRODUKSI PADI SAWAH MELALUI KELOMPOK TANI MENGGUNAKAN BAHASA PEMROGRAMAN - Dike, Radike (Sekolah Tinggi Manajemen Informatika dan Komputer GICI, 2017)
In the research the write directly did the research to the Kantor Kepala Desa Tanjung Pauh Mudik to get the data and to find the problems foced by the Kantor kepala Desa in the process produce paddy rice field through group farmer at office lead country side foreland. Currently, data processing system production rice field still counducted manual system. It makes the information gathered is in effective.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â The effont to apply the system is by comparing old systemand new system. To change the old system to the new system, firstly both systems have to be compared finally, choose the effective system for Kantor Kepala Desa or the instansion.